Efektivitas Membaca Buku Bersama untuk Menurunkan Kecemasan (pada Anak usia 4-6 tahun yang Baru Pertama Kali ke Dokter Gigi) - Veronica Febiany Sujana; Sri Redatin Retno Pudjiati (Provitae: Jurnal Psikologi Pendidikan, 2019)
Anxiety could occur to children going to dentist. Informing children about dental check-up could help to reduce anxiety; which is a learning process, one process could be done through vicarious learning by model observation. Storytelling by reading aloud with dialogic reading make student active, increases learning process by interaction with their peers and teacher. This research is aim to reduce anxiety for 4-6 years old (N-61) children going to dentist for their first time through reading a book together activity. Test scale use is Venham Picture Test (VPT). Research design is One group pre-test and post-test design with follow up after 1 week in the form of dental check-up. Book used on this activity titled “Cat and Dentist”, with main character’s courage to undergo dental check-up. Book was read by their teacher three times. Analysis result shows that through reading book together activity could lower anxiety toward dentist significantly for children of 4-6 years old that go to dentist first time between pre-rest and post-test 1 (z=-3,811 , p = 0,00 < 0,05), pre-test with post-test 2 (z = - 4,189, p = 0,00 < 0,05) and post-test 1 with post-test 2 (z=-2,184, p = 0,029 < 0,05). Keywords: Picture book, dialogic reading, anxiety, social constructivism.